2021
DOI: 10.29099/ijair.v6i1.325
|View full text |Cite
|
Sign up to set email alerts
|

Job Autonomy, workload, job stress and Intention to Leave on Millennial: A Literature Review

Abstract: This study aims to examine previous research to determine the effect of job autonomy and workload on the intention to leave mediated by job stress for millennial workers. This study applies various theories, namely the theory of Job Demand Resources (JDR), and Conservation of Resources (COR) to explain the relationship between variables. As a literature study article, this article contributes to developing a conceptual framework about intention to leave in the perspective of millennial workers. This article is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…In comparison to the other two variables, stress is the one that has the largest impact on the intention to leave. This study is consistent with earlier studies (Idham, 2022) on 100 workers at PT Satya Ardhia Angkasa (Outsourcing PT Angkasa Pura II Persero) at Soekarno-Hatta Airport Terminals 1, 2, and 3 and Sa & Praseti (2018) on 105 workers at PT Internusa Jaya Sejahtera Merauke (Gazali et al, 2021). Chen et al, (2011)found that Taiwanese bank employees likewise experienced the same outcomes.…”
Section: Stress At Work and The Intention To Leavesupporting
confidence: 91%
See 1 more Smart Citation
“…In comparison to the other two variables, stress is the one that has the largest impact on the intention to leave. This study is consistent with earlier studies (Idham, 2022) on 100 workers at PT Satya Ardhia Angkasa (Outsourcing PT Angkasa Pura II Persero) at Soekarno-Hatta Airport Terminals 1, 2, and 3 and Sa & Praseti (2018) on 105 workers at PT Internusa Jaya Sejahtera Merauke (Gazali et al, 2021). Chen et al, (2011)found that Taiwanese bank employees likewise experienced the same outcomes.…”
Section: Stress At Work and The Intention To Leavesupporting
confidence: 91%
“…The employee stress influences intention to leave is supported by research Biyan Wen, that there is a statistically significant correlation between role stress as a four-dimensional construct (i.e., conflict, ambiguity, qualitative overload, and quantitative overload) and burnout, which breeds turnover intention (Wen et al, 2020) and is further supported by many studies ((Gazali et al, (2021), Gantina & Ayuningtias (2021), Chen et al (2011), Yunita (2021. These indicate that job stress has a positive impact on intention to quit.…”
Section: Job Stress and Intention To Leavementioning
confidence: 85%